Bridging the Gap: Information Literacy and Learning in Online Undergraduate Courses. Issue 1 (3rd April 2019) - Zakharov, Wei; Maybee, Clarence
Abstract: This study explores how libraries can enhance information literacy in online undergraduate courses at Purdue University, a large Midwestern research university. The article investigates undergraduate students' perception of the importance and their awareness of libraries' services for online learning, challenges of using information to complete course assignments, and the ability to gather and evaluate information to complete online coursework. The findings contribute to four aspects of the Libraries' programmatic efforts to support undergraduate students taking online courses. These include showing a need for IL, helping students stay connected to resources and support, pedagogic strategies, and strategically targeting courses.